2018
DOI: 10.1029/2018gl079223
|View full text |Cite
|
Sign up to set email alerts
|

Warm Arctic, Increased Winter Sea Ice Growth?

Abstract: We explore current variability and future projections of winter Arctic sea ice thickness and growth using data from climate models and satellite observations. Winter ice thickness in the Community Earth System Model's Large Ensemble compares well against thickness estimates from the Pan‐Arctic Ice Ocean Modeling and Assimilation System and CryoSat‐2, despite some significant regional differences—for example, a high thickness bias in Community Earth System Model's Large Ensemble in the western Arctic. Differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 35 publications
8
56
0
Order By: Relevance
“…In regions of sea-ice loss, the DLR will be enhanced by increased ocean-toatmosphere heat and moisture fluxes (Screen & Simmonds, 2010). Although thin ice grows faster than thick ice , this negative feedback is projected to weaken (Petty et al, 2018), implying a strengthening role of atmospheric controls on winter sea ice growth. Although thin ice grows faster than thick ice , this negative feedback is projected to weaken (Petty et al, 2018), implying a strengthening role of atmospheric controls on winter sea ice growth.…”
Section: Physical Mechanismsmentioning
confidence: 99%
“…In regions of sea-ice loss, the DLR will be enhanced by increased ocean-toatmosphere heat and moisture fluxes (Screen & Simmonds, 2010). Although thin ice grows faster than thick ice , this negative feedback is projected to weaken (Petty et al, 2018), implying a strengthening role of atmospheric controls on winter sea ice growth. Although thin ice grows faster than thick ice , this negative feedback is projected to weaken (Petty et al, 2018), implying a strengthening role of atmospheric controls on winter sea ice growth.…”
Section: Physical Mechanismsmentioning
confidence: 99%
“…In the fall, the atmosphere cools rapidly, increasing the air-sea temperature gradient; the resulting increase in upward turbulent heat fluxes cools the ocean surface and warms and moistens the atmosphere. In a warming climate, sea ice loss is characterized by enhanced summer melt [10][11][12] and, correspondingly, enhanced winter lower-tropospheric warming [13][14][15] . The causal link between sea ice loss and surface-amplified wintertime warming has been confirmed in climate model experiments in which the sea ice component of a coupled ocean-atmosphere model is perturbed in isolation from other confounding factors [16][17][18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…We did not address the response of Arctic ice volume to near-surface ocean warming, although this has received significant attention in the literature in recent years, amid growing evidence of enhanced upper ocean radiative heating 10.1029/2020GL090236 of the Arctic Ocean (Moore et al, 2016;Timmermans et al, 2018). For example, Petty et al (2018) have reported sea ice growth as a lagged response to ocean and atmosphere warming in the Community Earth System Model Large Ensemble. In our experiments, SST warming is observed in some regions.…”
Section: Discussionmentioning
confidence: 99%